Examination of Lower Level Motion Mechanisms That Provide Information to Object Tracking: An Examination Using Dichoptic Stimulation. (November 2019) - Kanaya, Hidetoshi K.; Morita, Marie M.; Sato, Takao
In this study, we examined the operation of first- and second-order motion mechanisms with respect to object tracking using dichoptic presentation. A bistable apparent motion stimulus composed of four rectangles arranged in square- and diamond-shapes in every other frame was presented binocularly, monocularly, or dichoptically using a stereoscope. Since past motion studies showed that the first-order motion mechanism cannot function under dichoptic stimulation, we evaluated the upper temporal frequency limits of object tracking with dichoptic presentation and compared these results with those obtained with ordinary binocular or monocular (nondichoptic) presentation. We found that the temporal limits were 4 -5 Hz, regardless of the viewing conditions. These limits are similar to those for within-attribute (first- and second-order) object tracking (4 -5 Hz) obtained in our previous study. Thus, this putative mechanism may be responsible for object tracking, based only on second-order components, even in the case of first-order stimuli.